Phát triển cụm liên kết ngành nông nghiệp ở Việt Nam: Trường hợp nghiên cứu với ngành tiêu ở vùng Tây Nguyên - Lưu Văn, Duy; Lê Thị Thu, Hương; Võ Kim, Chung (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
In the context of globalization, the agricultural sector of Vietnam is transforming to improve competitiveness in the global market. One of the potential solutions is the development of agro-based clusters. This study aims to analyze the preconditions for developing the pepper clusters in Central Highland, Vietnam based on secondary data and primary data from a survey with 430 samples from 5 main actors across 4 provinces in the region in 2021. The study found out that the Central Highland has many favorable conditions in terms of natural and social conditions and the concentration and specialization to develop the pepper clusters. However, conditions such as operating institutions, and the leading role of key enterprises in cooperation in production and business are the main barriers hindering the development of the pepper clusters. Therefore, the policy of agro-based clusters development should give priority to regional spatial reorganization, enhance innovation, and strengthen support for factors involving in agro-based clusters.